Dental Caries Prevalence in the Children of the District of Mosqueiro in the City of Belém, State of Pará, Brazil - Helder Henrique Costa PINHEIRO; Izamir Carnevali de ARAUJO; Marizeli Viana de Aragão ARAÚJO; Alda França COSTA; Regina Fátima Feio BARROSO (Association of Support to Oral Health Research (APESB), 2006)
Objective: The study had the objective to check the dental caries prevalence in the children attend by the communitarian agents of health of the Program Health of the Family of the District of Mosqueiro, City of Belém, State of Pará, Brazil, with the purpose of subsidizing the projection of the actions of promotion, prevention and treatment of the staff of oral health. Method: 887 children were examined in the age groups from 18 to 36 months, 5 years and 12 years of age in accordance with the standards recommended by the WHO, checking the events of the caries in the studied population. Results: The caries prevalence in the population of the district of Mosqueiro to 18-36 months of age was 31.68%, progressing in spite of passing the ages, brought near attacking 63.69% of the 12-year-old children. The decayed, to be extracted, filled index (DEF index) to five years found in Mosqueiro went of 3.57 and the decayed, missing, filled index (DMF index) to 12 years went of 1,80. Regarding the marks proposed by the World Health Organization for the year of 2000, the reached only one was in the age of 12-year-old children, in which the DMF index of 1,80 was less than three. Conclusion: The caries prevalence in the population of Mosqueiro is due to implement effective actions for the control of the disease in this territory.